2017
DOI: 10.7224/1537-2073.2015-081
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Multiple Sclerosis in Hispanic Americans

Abstract: Background: Illness perceptions have been reported to be important determinants of multiple sclerosis (MS)-related well-being. Hispanic culture is defined by strong cultural beliefs in which illness is often perceived to arise from strong emotions. Understanding the perceptions of MS in Hispanic Americans may provide a better understanding of cultural barriers that may exist. The purpose of this study was to describe Hispanic American perceptions of MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…We found 10 studies supporting that SDOH disproportionately impacts Black and Hispanic and Latinx patients in MS outcomes, health care utilization, health behaviors, and lived experience with MS (Table 2; Figure 1B). We found no studies specific to SDOH that pertained to social and community context.…”
Section: Methodsmentioning
confidence: 75%
“…We found 10 studies supporting that SDOH disproportionately impacts Black and Hispanic and Latinx patients in MS outcomes, health care utilization, health behaviors, and lived experience with MS (Table 2; Figure 1B). We found no studies specific to SDOH that pertained to social and community context.…”
Section: Methodsmentioning
confidence: 75%
“…There is evidence supporting health literacy problems when it comes to MS-related disease modifying treatments and their realistic expectations, 39 poor access to specialty care, and illness perceptions affecting self-care. 40,41 Analysis of individuals with MS using the Independence Care System, a Medicaid long-term managed care plan in New York, found several deficiencies in the care of low-income minorities with MS where 30% had never seen an MS specialist and another 30% were not taking disease modifying treatments due to poor compliance and understanding of the drug. 39 Similar access problems were recently reported using a nationally representative dataset from the 2006–2013 Medical Expenditure Panel Survey where both blacks and Hispanics with MS were less likely to see a neurologist compared to whites (30% and 40% less, respectively).…”
Section: Disparities In Health Outcomesmentioning
confidence: 99%
“…Hispanic culture is characterized by strong values attached to family and cultural health beliefs. 94 , 95 While limited, a qualitative study using focus group responses and direct inquiries ( n = 106) 96 participants reported MS to be caused by an environmental encounter such as stress (44%) with stress being significantly more common in individuals who were US born compared to immigrant Hispanics (81% vs. 60%, p = 0.01). Sociocultural factors identified included cultural idioms such as fright ( susto ), or sadness ( tristeza ), which significantly were more common in individuals who were immigrants compared to US born (30% vs 9%, p = 0.04).…”
Section: Potential Risk Factors In Hispanics With Msmentioning
confidence: 99%